Complications Using Bioabsorbable Cross-Pin Femoral Fixation: A Case Report and Review of the Literature. (25th September 2011) - Hasan, Saqib; Nayyar, Samir; Onyekwelu, Ikemefuna; Kalra, Kunal; Gyftopoulos, Soterios; Jazrawi, Laith M.
Abstract : The use of bioabsorbable cross-pin transcondylar fixation has remained a viable option for femoral fixation in anterior cruciate ligament reconstruction. Although numerous biomechanical studies have demonstrated high fixation strength and minimal slippage with use of this method of fixation, there have been increasing reports of a variety of clinical complications associated with these implants. We reviewed the literature for all complications associated with the Bio-TransFix implant and present a case report of a patient status after ACL reconstruction using Bio-TransFix cross-pin femoral fixation with iliotibial band friction syndrome from a broken cross-pin four month post-operatively.